Proposed upgrading of Galeri Panglima Tentera Laut at Pangkalan Tentera Laut Lumut, Perak for Tentera Laut Diraja Malaysia / Muhammad Faizi Ahmad - Ahmad, Muhammad Faizi (Faculty of Architecture, Planning and Surveying, 2012)
As accomplishing the final stage of learning process,a comprhensive design proposal needs to be prepared by all of student.Concept and image that has been choosen not only has to be appropriate and suitable , but it must have strong impact towards the design purposes.some of information of the study is trough interview,observation,internet,book reference and all through the result from the case studies either locally or internationally.